Effect of Entrepreneurial Personality Traits on the Performance of Small-Scale Enterprises in Oyo State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Small-scale enterprises (SSEs) remain critical drivers of employment generation, innovation, and economic growth, however, their performance in Nigeria has continued to fluctuate due to managerial, environmental, and behavioural constraints. Increasing attention has therefore been directed toward entrepreneurial personality traits as determinants of enterprise success, yet empirical evidence on how such traits affect performance outcomes remains limited. This study was consequently undertaken to assess the effect of entrepreneurial personality traits on the performance of SSEs in Oyo State, Nigeria. Specifically, the study examined the effect of risk tolerance, entrepreneurial alertness, internal locus of control, and need for achievement on SSE performance. The study adopted a descriptive survey research design, and primary data were collected using a structured questionnaire administered to SSE owners. The population comprised 6,039 registered SSE owners operating across sectors as reported by the National Bureau of Statistics (2017), from which a sample size of 361 respondents was drawn using Krejcie and Morgan’s sampling formula. Data were analysed using descriptive statistics, including frequency and percentage, alongside multiple regression analysis. The findings revealed a strong positive correlation (R = .878) with an R-square value of .770, indicating that 77% of the variation in business growth performance was explained by entrepreneurial personality traits. Risk tolerance (0.792), entrepreneurial alertness (0.686), internal locus of control (0.761), and need for achievement (0.751) each demonstrated significant positive relationships with SSE performance. The study concluded that entrepreneurial personality traits significantly affected SSE performance and recommended integrating personality development into enterprise support programmes and policy initiatives.